TREATING PEDIATRIC ASTHMA WITH HOLISTIC APPROACHES OF TRADITIONAL CHINESE MEDICINE: A RETROSPECTIVE STUDY - Chang, Shun-Chang; Lee, Tsung-Chieh; Lee, Chia-Ying; Cheng, Tsung-Lin; Sun, Mao-Feng; Lo, Lun-Chien (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Asthma is a chronic disease increasingly found in children. To find more economical and efficient alternatives to treat pediatric asthma, the Bureau of National Health Insurance of Taiwan launched the Traditional Chinese Medicine Holistic Treatment Program (TCMHTP). The effect of traditional Chinese medicine (TCM) holistic treatments on pediatric asthma was evaluated based on data collected from the program.Materials and Methods: A retrospective study was performed by analyzing a dataset from Changhua Christian Hospital, Taiwan, between January 1st, 2006 and December 31st, 2010. Patients aged between 2 and 15 years, who had been diagnosed with asthma, and had participated in the TCMHTP were recruited, whereas those with other severe diseases were excluded. We analyzed the frequency of emergency department visits (EDV), inpatient admission rate (IAR), and length of hospitalization (LH) of the patients, before and after TCM treatments. Spectral analysis of heart rate variability (HRV) was also conducted. Results: Fifty-eight patients were recruited. The average age of the patients receiving TCM treatments was 5.67±3.03 years. The frequency of EDV decreased from 0.94±0.85 to 0.67±1.19 times annually (p=0.095), the annual IAR decreased from 0.62±0.78 to 0.26±0.67 (p=0.002) and the average LH decreased from 3.32±4.25 to 0.80±1.64 (p=0.000) days per year. Parasympathetically mediated HRV decreased significantly from 60.42±15.33 to 54.89±16.45 nu (p=0.016).Conclusion: The present study revealed that an appropriate period of TCM holistic treatment intervention can not only significantly lower exacerbations and hospitalization frequency but also reduce vagal tone in asthmatic children.